About Practical Problem Solving - Mutanen, Arto (Problemos, 2016)
Knowledge is, by definition, reliable and, hence, it can be applied to a variety of different problems. Nevertheless, in practical problem solving, we do not rely on mere truthful knowledge, but also on information which frames the practical acceptability. We are not looking for truthful solution but an optimal solution. Optimal solution is found out by optimizing some given (practical) parameters. The optimization is both theory based and practice based process. That is, practical problem solving is a human deliberation that interconnects theoretical and practical knowledge. So, the philosophical foundation of practical problem solving interconnects theoretical and practical philosophy. Especially ethical deliberation plays – or should play – central role in practical problem solving. The complexity of the advanced scientific knowledge needed in solving present day practical problems separates the people who know, from the people who do (decide). The situation makes immediate that we need some deeper pedagogical conviction: we need ecological education.